667.024.8 Design of a resource-efficient chain drive structure for the device drive that distributes the seed in the bunker to the linters - Xikmatillayev, Ismoilxon; Mamaxonov, A’zam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the article, a new chain drive structure with elastic elements is designed for the seed distribution device drive. At the same time, the parameters of the proposed chain drive are defined.